Synthesis of 13C‐labeled 5‐aminoimidazole‐4‐carboxamide‐1‐β‐D‐[13C5] ribofuranosyl 5′‐monophosphate. (15th July 2018) - Zarkin, Allison K.; Elkins, Phyllis D.; Gilbert, Amanda; Jester, Teresa L.; Seltzman, Herbert H.
Abstract : 5‐Aminoimidazole‐4‐carboxamide‐1‐β‐D‐[ 13 C5 ] ribofuranosyl 5′‐monophosphate ([ 13 C5 ribose] AICAR‐PO3 H2 ) (6 ) has been synthesized from [ 13 C5 ]adenosine. Incorporation of the mass‐label into [ 13 C5 ribose] AICAR‐PO3 H2 provides a useful standard to aid in metabolite identification and quantification in monitoring metabolic pathways. A synthetic route to the 13 C‐labeled compound has not been previously reported. Our method employs a hybrid enzymatic, and chemical synthesis approach that applies an enzymatic conversion from adenosine to inosine followed by a ring‐cleavage of the protected inosine. A direct phosphorylation of the resulting 2′, 3′‐isopropylidine acadesine (5 ) was developed to yield the title compound in 99% purity following ion exchange chromatography. Abstract : 5‐Aminoimidazole‐4‐carboxamide‐1‐β‐d‐[ 13 C5 ] ribofuranosyl 5′‐monophosphate ([ 13 C5 ribose] AICAR‐PO3 H2 ) (6 ) has been synthesized from [ 13 C5 ]adenosine. Incorporation of the mass label into [ 13 C5 ribose] AICAR‐PO3 H2, which has not been reported previously, provides a useful standard toward metabolite identification and quantification in metabolic pathways. Our method employs a hybrid enzymatic and chemical synthesis approach that applies an enzymatic conversion from adenosine to inosine followed by a ring cleavage. Phosphorylation of the resulting 2′, 3′‐isopropylidine acadesine (5 ) was developed to yield the title compound in 99% purity.